Unicentric Castleman's Disease Arising from an Intrapulmonary Lymph Node - Hideki Ota; Hideki Kawai; Tsubasa Matsuo (Case Reports in Surgery)
Castleman's disease is an uncommon lymphoproliferative disorder of unknown etiology, most often involving the mediastinum. It has 2 distinct clinical forms: unicentric and multicentric. Unicentric Castleman's disease arising from an intrapulmonary lymph node is rare, and establishing a preoperative diagnosis of this disease is very difficult mainly due to a lack of specific imaging features. We report a case of intrapulmonary unicentric Castleman's disease in an asymptomatic 19-year-old male patient who was accurately diagnosed by preoperative computed tomography (CT). The mass was incidentally found on a routine chest X-ray. A subsequent dynamic CT showed a well-defined, hypervascular, soft-tissue mass with small calcifications located in the perihilar area of the right lower lung. Three-dimensional CT (3D-CT) angiography indicated that the mass was receiving its blood supply through a vascular network at its surface that originated from 2 right bronchial arteries. The clinical history and CT findings were consistent with a diagnosis of unicentric Castleman's disease, and we safely and successfully removed the tumor via video-assisted thoracoscopic surgical lobectomy. This case shows that the imaging characteristics of these rare tumors on contrast-enhanced CT combined with 3D-CT angiography can be helpful in reliably establishing a correct preoperative diagnosis.